2019
DOI: 10.1002/cssc.201902096
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Conversion of C5 and C6 Sugars into Methyl Levulinate with the Addition of 1,3,5‐Trioxane

Abstract: The simultaneous conversion of C 5 andC 6 mixed sugarsi nto methyl levulinate (MLE) has emerged as av ersatile strategy to eliminate costly separation steps. However,t he traditional upgradingo fC 5 sugars into MLE is very complex as it requires both acid-catalyzed and hydrogenation processes. This study concerns the development of ao ne-pot,h ydrogenation-free conversion of C 5 sugarsi nto MLE over different acid catalysts at near-critical methanolconditions with the help of 1,3,5-trioxane. For the conversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The earlier studies utilize larger amounts of HM reagent, and/or obtain lower product and/or higher humins yields. [ 12–16 ] While, the present study utilizes a lower formaldehyde:furfural ratio and water as solvent, and reports lower humins yield at reasonably higher LA yields. Moreover, from the formaldehyde consumption data (Table S1, Supporting Information), it was evident that the formaldehyde consumed was relatively low at lower C F (2 wt%), and close to that required for the LA/HMF production.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The earlier studies utilize larger amounts of HM reagent, and/or obtain lower product and/or higher humins yields. [ 12–16 ] While, the present study utilizes a lower formaldehyde:furfural ratio and water as solvent, and reports lower humins yield at reasonably higher LA yields. Moreover, from the formaldehyde consumption data (Table S1, Supporting Information), it was evident that the formaldehyde consumed was relatively low at lower C F (2 wt%), and close to that required for the LA/HMF production.…”
Section: Resultsmentioning
confidence: 94%
“…obtained a maximum methyl levulinate (MLE) yield of 50.4% in the conversion of glucose and xylose over H‐β zeolite using 1,3,5‐trioxane/methanol mixture. [ 12 ] Zhang et al. [ 13 ] reported a maximum yield of 68% MLE at 97% furfural conversion using D008 solid acid resin in dimethoxymethane (DMM)/methanol solvent system.…”
Section: Introductionmentioning
confidence: 99%
“…To begin with, commercially available H-beta25, which has been applied for the synthesis of ML from sugars, , was chosen as the catalyst for the conversion of HMF to ML in methanol. The reaction condition was initially set at 170 °C for 50 min under 10 bar N 2 , and 52% yield of ML was obtained.…”
Section: Resultsmentioning
confidence: 99%
“…15 Lyu et al utilized a 1,3,5-trioxane/methanol mixture to convert C5/C6 sugars to MLE. The maximum MLE yields of 47.4 and 50.4% were obtained with xylose (1 wt%) and a glucose + xylose (1 wt%) mixture as feedstocks, respectively, over the Hβ zeolite at 160 °C and 18 h. 16 Zhang et al reported the production of an MLE and LA mixture using DMM/methanol in the transformation of furan (7.1 wt%) over the D008 resin. MLE was obtained in a maximum yield of 67.9% with 97.2% furan conversion at 170 °C and 90 min.…”
Section: Introductionmentioning
confidence: 99%